A hybrid Bloom filter location update algorithm for wireless cellular systems - Yuen, W.H.A.; Wing Shing Wong (1997 IEEE International Conference on Communications, 1997)
A hybrid Bloom filter location update algorithm is proposed for wireless cellular systems. This belongs to a new category of algorithms characterized by contention free access of uplink control channels during location update. Two or more mobile units are permitted to register with a base station simultaneously without contention on the uplink channel. The location updating procedure is hybrid in the sense that it could be temporally or geographically triggered. Based on the location information stored in all base stations, Bloom filtering is used to select cells to be paged to locate the targeted mobile unit. The performance of this scheme is compared to other algorithms previous proposed. Numerical results shows that the new algorithm requires less combined location update and paging bandwidth than other algorithms.